Vancomycin treatment is a risk factor for vancomycin-nonsusceptible Staphylococcus capitis sepsis in preterm neonates. (November 2017) - Butin, M.; Rasigade, J.-P.; Subtil, F.; Martins-Simões, P.; Pralong, C.; Freydière, A.-M.; Vandenesch, F.; Tigaud, S.; Picaud, J.-C.; Laurent, F.
Abstract: Objectives: Multidrug-resistant, vancomycin-nonsusceptible Staphylococcus capitis is an emerging cause worldwide of late-onset sepsis (LOS) in preterm neonates. The pathophysiology and risk factors for S. capitis –related LOS are poorly understood, but we hypothesized that S. capitis LOS follows translocation from the gut microbiota rather than catheter invasion. The objective of this study was to investigate the risk factors of S. capitis LOS and gut colonization. Methods: We conducted a prospective single-centre cohort study of patients hospitalized in a tertiary-care unit (Lyon, France) from June 2011 to January 2012. S. capitis gut colonization was determined weekly from stool cultures. The determinants of gut colonization and LOS were established by multivariate Cox proportional hazards models. Results: Eighty-three (36.2%) of 229 patients had S. capitis –positive stool culture, and 28 (12.2%) developed S. capitis LOS during hospitalization. Independent risk factors for S. capitis LOS included prior administration of vancomycin independent of a previous LOS episode (hazard ratio 6.44, 95% confidence interval 2.15–19.3, p 0.001) and low birth weight (hazard ratio 0.72 per 100 g increase, 95% confidence interval 0.55–0.95, p 0.02). The prior administration of vancomycin was also an independent risk factor for S. capitis colonization (hazard ratio 3.45, 95% confidence interval 2.07–5.76, p <0.001), particularly in the first week of life and in noncolonized neonates. Conclusions: Neonates treated with vancomycin are at a higher risk of LOS caused by vancomycin-nonsusceptible S. capitis. The use of vancomycin in neonates must urgently be optimized to limit the selection of vancomycin-nonsusceptible strains, for which alternative antibiotics are lacking.